Media portrayals of assisted suicide before, during, and after legalization changes: content analysis of the reporting in Austrian newspapers - Pürcher, Paul; Till, Benedikt; Niederkrotenthaler, Thomas (Frontiers in Psychiatry, 2025)
IntroductionAssisted suicide (AS) was legalized in Austria in 2022 for adults in specific circumstances, adding Austria to a list of several countries where AS has recently been legalized. The topic has been discussed controversially in the Austrian public, which has been reflected in the media reporting. Information about the content of media reports on AS is currently lacking although it is important from a suicide prevention perspective. The aim of this study was to analyze newspaper media items on AS from Austrian daily newspapers based on media guidelines for the reporting on suicide and to adapt them in the process to the specific topic of AS.MethodsMedia items from 11 Austrian daily newspapers from the time period 2017 to 2022 were retrieved based on 12 predefined keywords. A total of n = 906 articles were analyzed with regard to 12 characteristics advised against in media guidelines and 7 recommended characteristics. We compared the quality of media items between three time periods: period 1 (before the initiation of legislation change regarding AS in Austria, 01/2017–12/2019), period 2 (around the decision of legalization of AS, 01/2020–12/2021), and period 3 (after the implementation of AS in Austria, 01/2022–12/2022).ResultsSeveral characteristics advised against in suicide reporting guidelines (e.g., romanticization/glorification of AS) were relatively frequent across all three time periods, while recommended characteristics (e.g., references to mental health services) were less common. Comparison across time showed that stigmatization and romanticization/glorification, though prevalent, declined after AS was implemented, whereas reporting on epidemics and waves of AS peaked immediately before its implementation.DiscussionThis content analysis revealed distinct patterns in media reporting on AS and showed that reports were less aligned with media guidelines than previous analyses on non-assisted suicide. Some patterns identified across all time periods, particularly tendencies to stigmatize or romanticize AS before the legislation, likely reflect polarized public attitudes, which warrant attention in education efforts. This research highlights the importance of specific aspects of media guidelines during public debate on AS and the need to tailor them to this topic.